AB0769 Sonographic signs of enthesitis in established psoriatic arthritis and healthy volunteers. (15th June 2017) - Wervers, K; Herrings, I; Luime, JJ; Moed, M; Tchetverikov, I; Gerards, AH; Hazes, JMW; Vis, M
Abstract : Background: Previous research in our group showed that sonographic signs of enthesitis are present in early and established PsA, but in young healthy volunteers as well. The Madrid Sonographic Enthesitis Index (MASEI) was only able to differentiate between patients and healthy volunteers after excluding knee enthesis thickness from the score and semi-quantitative scoring of Power Doppler (PD) signal (1). Objectives: We aim to validate the modified MASEI in a larger cohort of established PsA patients and healthy volunteers. Methods: Established PsA patients and healthy volunteers aged 35–55 were asked to participate in this cross-sectional study, irrespective of presence of enthesitis complaints. The triceps, quadriceps, proximal and distal patellar and Achilles tendon and plantar fascia (i.e. the locations of the MASEI) and the common extensor insertion at the lateral epicondyle of the elbow were evaluated sonographically for structural changes (i.e. erosions, calcifications and structure) and active inflammation (thickness, bursitis and PD). Results: 84 established PsA patients and 25 healthy volunteers participated. Sonographic structural changes and one or two spots of PD signal were common in both groups. The modified MASEI was significantly higher in PsA patients (median 12 (IQR 7.25–17) vs. 7.5 (5–9), P<0.001), while the original MASEI did not differ significantly (Table 1 ). Confluent PD over a larger area was only seen in 8% of the established PsA patients. Structural damage on ultrasound was more pronounced in the patients compared to the healthy volunteers. Number of PD locations and PD score did not distinguish the two groups. Conclusions: Inflammatory and structural changes of the enthesis measured with ultrasound are common in both unselected PsA patients and healthy volunteers, but more pronounced in established PsA patients. References: Wervers K, Rasappu N, Vis M, Tchetverikov I, Kok MR, Gerards AH, et al. AB0733 Masei Shows Substantial Changes in The Entheses of Young Healthy Volunteers – Amending Its PD Score and Excluding Knee Entheses Thickness Provides Better Discrimination of Enthesitis in Psoriatic Arthritis Patients. Ann Rheum Dis 2016;75:1155. Disclosure of Interest: None declared